Flow Experiences During Visuomotor Skill Acquisition Reflect Deviation From a Power-Law Learning Curve, but Not Overall Level of Skill - Cowley, Benjamin Ultan; Palomäki, Jussi; Tammi, Tuisku; Frantsi, Roosa; Inkilä, Ville-Pekka; Lehtonen, Noora; Pölönen, Pasi; Vepsäläinen, Juha; Lappi, Otto (Frontiers in Psychology, 2019)
Flow is a state of `optimal experience' that arises when skill and task demands match. Flow has been well studied in psychology using a range of self-report and experimental methods; with most research typically focusing on how Flow is elicited by a particular task. Here, we focus on how the experience of Flow changes during task skill development. We present a longitudinal experimental study of learning, wherein participants (N = 9) play a novel steering-game task designed to elicit Flow by matching skill and demand, and providing clear goals and feedback. Experimental design involves extensive in-depth measurement of behaviour, physiology, and Flow self-reports over two weeks of 40 game trials in eight sessions. Here we report behavioural results, which are both strikingly similar and strong within each participant. We find that the game induces a near-constant state of elevated Flow. We further find that the variation in Flow across all trials is less affected by overall performance improvement than by deviation of performance from the expected value predicted by a power law model of learning.